Structural model of the nucleotide-binding conserved component of periplasmic permeases. - Mimura, C S (1991)
The amino acid sequences of 17 bacterial membrane proteins that are components of periplasmic permeases and function in the uptake of a variety of small molecules and ions are highly homologous to each other and contain sequence motifs characteristic of nucleotide-binding proteins. These proteins are known to bind ATP and are postulated to be the energy-coupling components of the permeases. Several medically important eukaryotic proteins, including the multidrug-resistance transporters and the protein encoded by the cystic fibrosis gene, are also homologous to this family. By multiple sequence alignment of these 17 proteins, the consensus sequence, secondary structure, and surface exposure were predicted. The secondary structural motifs that are conserved among nucleotide-binding proteins were identified in adenylate kinase, p21ras, and elongation factor Tu by superposition of their known tertiary structures. The equivalent secondary structural elements in the predicted conserved component were located. These, together with sequence information, served as guides for alignment with adenylate kinase. A model for the structure of the ATP-binding domain of the permease proteins is proposed by analogy to the adenylate kinase structure. The characteristics of several permease mutations and biochemical data lend support to the model.